Description of two mass species of Pacific copepods in terms of two polymorphic loci - K I Afanas extquotesingleyev; Mikhail V Flint; A N Fetisov (PANGAEA, 1989)
Population genetics of two species of mass copepods Undinula darwini and Calanus australis, with different range types, is investigated. Both species exhibit considerable genetic diversity, especially C. australis (observed heterozygoticity = 0.36), which inhabits a variable biotope in the zone of the Peru current. Samples of both species exhibited highly significant genetic heterogeneity as well as heterozygote deficiency compared with the situation expected from the Hardy-Weinberg law. Contribution of distance isolation to genetic differentiation of populations is estimated. Gene drift is discussed as a source of heterogeneity in populations of planktic copepods. Possible aspects of population genetic research on marine plank-tic crustaceans are discussed.
Supplement to: Afanas extquotesingleyev, KI et al. (1989): Population genetics of two mass species of Pacific Ocean copepods. Oceanology, 29(2), 225-231